PrimPol-deficient cells exhibit a pronounced G2 checkpoint response following UV damage. Issue 7 (2nd April 2016) - Bailey, Laura J.; Bianchi, Julie; Hégarat, Nadia; Hochegger, Helfrid; Doherty, Aidan J.
ABSTRACT: PrimPol is a recently identified member of the archaeo-eukaryote primase (AEP) family of primase-polymerases. It has been shown that this mitochondrial and nuclear localized enzyme plays roles in the maintenance of both unperturbed replication fork progression and in the bypass of lesions after DNA damage. Here, we utilized an avian (DT40) knockout cell line to further study the consequences of loss of PrimPol ( PrimPol −/− ) on the downstream maintenance of cells after UV damage. We report that PrimPol −/− cells are more sensitive to UV-C irradiation in colony survival assays than Pol η-deficient cells. Although this increased UV sensitivity is not evident in cell viability assays, we show that this discrepancy is due to an enhanced checkpoint arrest after UV-C damage in the absence of PrimPol. PrimPol −/− arrested cells become stalled in G2, where they are protected from UV-induced cell death. Despite lacking an enzyme required for the bypass and maintenance of replication fork progression in the presence of UV damage, we show that PrimPol −/− cells actually have an advantage in the presence of a Chk1 inhibitor due to their slow progression through S-phase.